2020
DOI: 10.1371/journal.pone.0228776
|View full text |Cite
|
Sign up to set email alerts
|

Islands as a crossroad of evolutionary lineages: A case study of Centaurea sect. Centaurea (Compositae) from Sardinia (Mediterranean Basin)

Abstract: The Mediterranean Basin is a biodiversity hotspot, where islands play a key role because of their high biological diversity, degree of endemicity and human pressure. One of these islands, Sardinia, is a good evolutionary laboratory, especially for the study of complex genera, such as Centaurea. In particular, endemic species of Centaurea sect. Centaurea from Sardinia provides an interesting case study of plant evolution on continental islands. We attempted to clarify the processes leading to the diversificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Based on Carvajal-Endara et al (2017) the establishment of a lineage seems to be the bigger hurdle than dispersal. While our study focused on particular island systems that have been well studied, the patterns of species diversification on islands that have emerged may be more general to other island systems (e.g., López-Alvarado et al, 2020 ). Other island systems would be interesting to evaluate for these larger-scale patterns, as studies on their specific flora are becoming available (e.g., Sardinia – López-Alvarado et al, 2020 ; Balearic Islands – Rosselló and Castro, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Carvajal-Endara et al (2017) the establishment of a lineage seems to be the bigger hurdle than dispersal. While our study focused on particular island systems that have been well studied, the patterns of species diversification on islands that have emerged may be more general to other island systems (e.g., López-Alvarado et al, 2020 ). Other island systems would be interesting to evaluate for these larger-scale patterns, as studies on their specific flora are becoming available (e.g., Sardinia – López-Alvarado et al, 2020 ; Balearic Islands – Rosselló and Castro, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…While our study focused on particular island systems that have been well studied, the patterns of species diversification on islands that have emerged may be more general to other island systems (e.g., López-Alvarado et al, 2020 ). Other island systems would be interesting to evaluate for these larger-scale patterns, as studies on their specific flora are becoming available (e.g., Sardinia – López-Alvarado et al, 2020 ; Balearic Islands – Rosselló and Castro, 2008 ). Indeed, Rice et al (2019) , in their global analysis of polyploid biogeography, find high levels of polyploidy on several island systems, which mainly relate to the climatic conditions and predominance of perennial taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, yildirim et al These few studies, however, did not include any of the Centaurea species found in Egypt in their analysis and used less reproducible marker systems (RAPD, SSR, ISSR etc.) [36][37][38][39]. With the evolution of many improved novel marker techniques, currently, they have become a not preferred marker technique in plant genetic diversity studies.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, palaeoendemic (systematically isolated species), schizoendemic (phenotypically and karyologically similar species originated by allopatric speciation from a widespread ancestor) and neoendemic (recently diversified species or still diversifying lineages) taxa were defined. However, there is lack of phylogenetic and phylogeographic studies for many taxa, and thus the feasibility of this approach is far from being achieved, despite the increasing number of recent scientific papers are shedding light on this crucial aspect [e.g., [4][5][6][7][8]. The first attempt to organically describe the endemic vascular flora of Sardinia (consisting in the presentation of 202 taxa on the Bulletin of the Sardinian Society of Natural Sciences by Arrigoni et al [9]) was based on this first approach.…”
Section: Introductionmentioning
confidence: 99%